PEMANFAATAN DAUN KUMIS KUCING SEBAGAI OBAT HERBAL UNTUK MENGOBATI BATU GINJAL DI DESA ORAHILI FONDRAKO KECAMATAN ULUSUSUA - Albianus Gaurifa; Depirman Fatemaluo; Ester Sarumaha; Septiaman Nining W. Laowo; Fiki Halawa; Meila Endang K.Giawa; Okti Mesrtawati Ndruru; Putra Jaya Buulolo; Putra Jodi Halawa; Selvin Laia; Feriawati Mendrofa; Adam Smith Bago (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
This research aims to examine the utilization of cat’s whiskers leaves (Orthosiphon aristatus) as a traditional herbal medicine in treating kidney stones in Orahili Fondrako Village, Ulususua District. Kidney stones are among the common illnesses suffered by rural communities due to insufficient fluid intake, unbalanced diets, and environmental factors. In the midst of limited access to modern healthcare services, the local community relies on traditional medicinal plants as an alternative treatment, one of which is cat’s whiskers leaves. The method used in this research is a qualitative approach with data collection techniques including in-depth interviews, field observations, and literature studies. The research informants consist of traditional leaders, local healers, and residents who have used cat’s whiskers leaves for kidney stone treatment. The findings show that the leaves are commonly consumed in the form of boiled decoctions taken regularly for several days until the symptoms of kidney stones subside. The community believes that the diuretic properties of cat’s whiskers leaves help facilitate urination and naturally dissolve kidney stones. In addition, this research also reveals the existence of inherited traditional knowledge that plays an important role in the preservation and utilization of medicinal plants in the village. However, the use of cat’s whiskers leaves remains traditional and is not yet supported by scientifically standardized dosages. Therefore, further in-depth studies are needed to examine the effectiveness and safety of cat’s whiskers leaves through clinical trials.